Tinjauan Literatur Sistematis Optimalisasi Steam Flooding untuk Peningkatan Produksi pada Lapangan Minyak - Chanaya, Diandra Chaswatul; Ulfah, Baiq Maulinda (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This systematic literature review discusses the optimisation of steam flooding as one of the important enhanced oil recovery (EOR) methods for heavy oil production. Steam flooding is proven to reduce oil viscosity, increase fluid mobility, and improve sweep efficiency. However, the main challenges include high steam-oil ratio (SOR), large energy requirements, reservoir heterogeneity, and operational costs. Through a Systematic Literature Review (SLR) of 5 selected journals published in 2023-2025, this study identifies optimisation strategies such as injection pattern design, steam quality control, use of supporting technologies such as horizontal wells and solvent injection, and renewable energy integration. The results show that technical optimisation includes injection pattern design, steam rate and quality control, well configuration (including the use of horizontal wells), and remedial stimulation through acidising. On the economic side, the focus was on reducing Capex and Opex, increasing Net Present Value (NPV) and Internal Rate of Return (IRR), and oil price sensitivity. In addition, innovation in the form of Solar Enhanced Oil Recovery (S-EOR) offers a sustainable solution in reducing energy costs and reducing carbon emissions.